2013
DOI: 10.1159/000342316
|View full text |Cite
|
Sign up to set email alerts
|

The Steroid Controversy: Where Are We?

Abstract: Dexamethasone is widely administered to children during elective tonsillectomy to reduce the rate of postoperative nausea and vomiting, as well as decrease postoperative use of pain medications. Over the past two decades, there has been a wealth of literature advocating the practice that has led to endorsement by a variety of anesthesia and otolaryngology professional associations. However, the publication of a trial that was halted due to a potential dose-dependent association between postoperative hemorrhage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
7
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 67 publications
1
7
0
1
Order By: Relevance
“…18 Subsequent safety evidence published during or after the postguideline period in this study has been conflicting, and thus the use of dexamethasone has been a point of controversy. 19 A noninferiority trial found that there was no increased risk of bleeding associated with dexamethasone; however, this trial has been criticized as having set an inappropriately large noninferiority margin for bleeding that necessitated reoperation (ie, 5%). 20,21 A meta-analysis and a large observational study concluded that there is no clinically important risk of bleeding associated with dexamethasone use.…”
Section: Discussionmentioning
confidence: 99%
“…18 Subsequent safety evidence published during or after the postguideline period in this study has been conflicting, and thus the use of dexamethasone has been a point of controversy. 19 A noninferiority trial found that there was no increased risk of bleeding associated with dexamethasone; however, this trial has been criticized as having set an inappropriately large noninferiority margin for bleeding that necessitated reoperation (ie, 5%). 20,21 A meta-analysis and a large observational study concluded that there is no clinically important risk of bleeding associated with dexamethasone use.…”
Section: Discussionmentioning
confidence: 99%
“…Our large observational study combined with this body of evidence from small RCTs supports the safety of dexamethasone and these recommendations for the routine use of dexamethasone in children. 3,8 …”
Section: Discussionmentioning
confidence: 99%
“…There has been controversy on whether dexamethasone increases bleeding risk. 8 It has been hypothesized that dexamethasone inhibits postoperative healing processes resulting in increased risk of bleeding. 9 Analysis of bleeding as a secondary outcome in several small trials found postoperative bleeding to be increased with dexamethasone use.…”
mentioning
confidence: 99%
“…17 That 2008 study was an outlier in the dexamethasone literature, and its statistical analyses have been extensively questioned. 18 Ibuprofen and other nonselective NSAIDs face precisely the same challenge if a bleeding risk rationale-however unproven-is also considered to be true.…”
mentioning
confidence: 99%
“…17 Cette étude fait figure d'anomalie dans la littérature portant sur la dexaméthasone, et ses analyses statistiques ont depuis été considérablement remises en question. 18 L'ibuprofène et les autres AINS non sélectifs seront confrontés aux mêmes difficultés d'adoption s'il existe la moindre croyance-qu'elle soit avérée ou non-qu'il y a un risque de saignement. À la lumière de cet exemple édifiant, et malgré les directives 13,15 préconisant son utilisation, nous ne pouvons pas nous attendre à ce que l'ibuprofène soit adopté de façon universelle par les médecins dans un avenir proche.…”
unclassified